Standardizing Zebrafish Behavioral Paradigms Across Life Stages: An Effort Towards Translational Pharmacology - Petersen, Barbara Dutra; Bertoncello, Kanandra Taisa; Bonan, Carla Denise (Frontiers in Pharmacology, 2022)
Zebrafish is a prominent vertebrate model, with many of its advantages related to its development, life cycle, and translational ability. While a great number of behavioral phenotypes and tasks to evaluate them are available, longitudinal studies across zebrafish life stages are scarce and made challenging because of the differences between protocols and endpoints assessed at each life stage. In this mini review, we highlight the relevance that longitudinal studies could have for neurobehavioral pharmacology using this model. We also present possible strategies to standardize behavior endpoints in domains related to human diseases throughout the life cycle, especially between larvae and adult fish. Furthermore, we discuss the remaining difficulties of these analyses and explore future advances needed to bridge this knowledge gap.